(untitled) (Jahangirnagar University Journal of Biological Sciences, 2020)
The occurrence of a total of 31 species of pteridophytes under 20 genera and 13 families in Narsingdi district were confirmed. Pteridaceae with 11 species was found as the largest family, which was followed by Salviniaceae and Polypodiaceae consisted of four species each and Thelypteridaceae with three species. Each of the rest nine families was represented by only one species. Pteris with six species was found as the largest genus, which was followed by Salvinia with three species, and Adiantum, Ceratopteris, Pyrrosia and Cyclosorus with two species each. Each of the rest 14 genera was represented by only one species. Among these species, 21 were found as terrestrial, two as both terrestrial and semiaquatic, four as aquatic and other four as epiphytic. The occurrence of Tectaria chattagrammica Ching, listed as DD (Data Deficient) in Red Data Book of Bangladesh, was common with natural regeneration in this district. Jahangirnagar University J. Biol. Sci. 8(2): 13-24, 2019 (December)